The Impact of Limited Organisational and Community Resources on Novice Child Protection Workers: A Queensland Example. (4th July 2013) - Bates, Annerley
Abstract : A high turnover of staff at the Queensland statutory child protection agency, combined with a lack of experienced prospective employees, means that the agency is increasingly relying on new university graduates. However, the availability of resources is a risk to the continued engagement of child protection workers because they do not feel that they are able to adequately service the clients who they work with, and is one reason why they may choose to leave the agency. In order to gain a greater understanding of how graduate child protection workers perceive both organisational and community resourcing, this study interviewed 20 child protection workers who were still in their first 12 months of employment in the agency. The results suggest that insufficient staffing within the agency affected the work of the child protection workers. Participants identified that additional organisational resources of that which would improve the capacity of child protection workers to fulfil their role in a more efficient and safe manner included motor vehicles and administrative support. Participants expressed the view that resources external to the organisation were necessary to promote practice and improve outcomes for children and families. In the absence of additional resources being made available, effectively allocating resources within child protection offices, as well as encouraging the workers to develop their knowledge of available resources, should help address this issue. Copyright © 2013 John Wiley & Sons, Ltd. 'The results suggest that insufficient staffing within the agency affected the work of the child protection workers' Key Practitioner Messages: Dissatisfaction with resourcing both within a statutory child protection agency and within community‐based organisations external to the agency affect child protection workers' job satisfaction. Effectively allocating existing resources within child protection offices and encouraging new child protection workers to develop their awareness of external resources should assist these practitioners to fully utilise the resources available to assist children.